Analysis of Japanese consumers' attitudes toward the digital transformation of OTC medicine purchase behavior and eHealth literacy: an online survey for digital experience design - Tang, Guyue; Izumi, Kairi; Izumisawa, Megumi; Koyama, Shinichi (Frontiers in Digital Health, 2023)
Introduction: Since the enactment of the revised Pharmaceutical Affairs Act in Japan in 2009, self-medication practices have increased in the country. However, studies report that consumers pay little attention to the medication facts and risks indicated on the packages of over-the-counter (OTC) medicines, which could be a potential risk. Since the COVID-19 pandemic, the digital transformation of purchasing OTC medicines has progressed. As an appropriate design for the digital transformation is likely to improve consumers’ literacy and them obtaining medical information, this study systematically examines Japanese consumers’ attitudes toward the digital transformation of OTC medicine purchase behavior and its correlation to eHealth literacy, exploring an appropriate digital experience design in purchasing OTC medicine. Methods: Participants from the Greater Tokyo Area of Japan participated in an online survey. Consumers’ current behavior and preferences in accessing OTC medicine, receiving medication guidance, and obtaining medical information were examined. eHealth literacy was assessed using the J-eHEALS. Descriptive statistics, text mining, and thematic analysis were conducted to answer research questions. Results: Over 89% of the respondents who had experience in purchasing OTC medicines preferred local pharmacies or stores rather than online purchasing, p < 0.001. Obtaining medicine guidance in pharmacies or stores was the main preference over other approaches, p < 0.001. Furthermore, most of the participants accepted selecting medicine on shelves and digital screens in-store. However, they were accustomed to using smartphones to obtain additional information at the pharmacy or drug store, p < 0.001; this behavior was positively correlated with eHealth literacy, p < 0.001. Conclusions: Japanese consumers are seeking a combination of conventional and digital behaviors for purchasing OTC medicine rather than opting for a particular method. Most consumers prefer purchasing and receiving instructions in-store while searching for additional decision-making information online. eHealth literacy is positively associated with digital behaviors of OTC medicine information acquisition but less associated with medicine purchases and selections. The hybrid digital experience design may enhance the OTC medicine purchase experience and reduce potential risks by providing appropriate information.